Mechanisms of Cognitive Impairment in Depression. May Probiotics Help? - Dobielska, Maria; Bartosik, Natalia Karina; Zyzik, Kamil A.; Kowalczyk, Edward; Karbownik, Michał Seweryn (Frontiers in Psychiatry, 2022)
Depression is the major cause of disability globally. Apart from lowered mood and accompanying symptoms, it leads to cognitive impairment that altogether predicts disadvantaged social functioning. Reduced cognitive function in depression appears a bit neglected in the field of clinical and molecular psychiatry, while it is estimated to occur in two-thirds of depressed patients and persist in at least one third of remitted patients. This problem, therefore, requires elucidation at the biomolecular and system levels and calls for improvement in therapeutic approach. In this review study, we address the above-mentioned issues by discussing putative mechanisms of cognitive decline in depression: 1) increased oxidative stress and 2) inflammation, 3) disturbed hypothalamus-pituitary-adrenals axis, and 4) reduced monoamines functionality. Moreover, we acknowledge additional underpinnings of cognitive impairment in depressed elderly: 5) vascular-originated brain ischemia and 6) amyloid-beta plaque accumulation. Additionally, by reviewing molecular, pre-clinical and clinical evidence, we propose gut microbiota-targeted strategies as potential adjuvant therapeutics. The study provides a consolidated source of knowledge regarding mechanisms of cognitive impairment in depression and may path the way towards improved treatment options.